Uplift : Visual Culture at the Banff School of Fine Arts - Reichwein, PearlAnn, 1966-; Wall, Karen L. (Karen Linda), 1955- (Book collections on Project MUSE., 2020)
"In 1933, the Banff School was established as a summer outreach program of the University of Alberta, offering a single course in drama. Since then, it has become a renowned cultural destination and educational institution, today known as the Banff Centre for Arts and Creativity. As PearlAnn Reichwein and Karen Wall recount in this engaging history, over its first four decades the school produced and circulated ideals of culture and liberal democratic citizenship that were intrinsic to the development of modern Canada. Uplift traces the role of the school in shaping arts and cultural education, as reflected in its array of interests from the artistic to the political, economic, and ideological. Situated within Banff National Park, the school and its surroundings combined stunning natural scenery and cultural capital in a symbolic national landscape. In an era of unstable cultural policy and state support for the arts, Uplift offers a nuanced account of one particular engine of nation building and tourism development. It draws attention to the past and present place of fine arts, culture, and the humanities in public education and in Canada's history, exploring what they mean to democracy, citizenship, and a life well lived."--